Women’s Empowerment in Agrifood Governance (WEAGov) assessment framework: A pilot study in Nigeria - Ragasa, Catherine; Kyle, Jordan; Onoja, Anthony Ojonimi; Achika, Anthonia I.; Adejoh, Stella O.; Onyenekwe, Chinasa S; Koledoye, Gbenga; Ujor, Gloria C.; Nwali, Perpetual Nkechi (International Food Policy Research Institute, 2023)
Women’s equal participation and leadership in political and public life can boost a country’s long-run economic growth, foster social inclusion, and help countries reach the 2030 Sustainable Development Goals (SDGs). Beyond these important outcomes, women’s inclusion in public life is a basic human right: women deserve a role in making decisions, controlling resources, and shaping policies. Despite the importance of women’s voices and their empowerment in policy and decision-making processes, it is far easier to lament their absence than to define and measure them. We know that political empowerment, measured in terms of the share of women in government ministries and parliament, is low and is the weakest dimension in the Global Gender Gap. Yet such national statistics, while important and informative, risk mismeasuring women’s participation and influence in public life and do not give policymakers and advocacy organizations traction on specific gaps and opportunities for increasing women’s voice in policymaking. With this situation in mind and focusing on agrifood systems, which are crucial for delivering the SDGs, we developed an assessment framework—Women’s Empowerment in Agrifood Governance (WEAGov)— to assess women’s voice and empowerment in national policy processes in agrifood systems. This paper presents the first pilot-testing of WEAGov in Nigeria. In this paper, we present how the WEAGov tool works in the Nigerian context, analyze the data, and provide diagnostic on the status of women’s voice and empowerment in the agrifood policy process. As discussed in this paper, the pilot-testing in Nigeria provides useful lessons toward improving the measurement for future use and provides valuable policy insights on critical entry points for increasing women’s voice and empowerment in the national agrifood policy process.